THE HURDLES OF THE TEACHER IN THE PRACTICE OF TARGET LANGUAGE IN THE INDONESIAN EFL JUNIOR HIGH SCHOOL - Dzul Rachman; Dedi Rahman Nur; Sunarti Sunarti; Rani Herning Puspita (Universitas Muhammadiyah Kalimantan Timur, 2019)
In teaching learning process, the target language is an important thing which has been noticed by the teacher. The phenomenon about misunderstanding language is not only occurring in daily life with soft conversation but also in the formal education. In education event, when the teacher teaches students in the classroom, they use target language during activities. The aims of this study were to describe the teacher’s hurdles in using target language at first grade of Junior high school and how the teacher delivered instruction by using target language at EFL class. This study used a descriptive qualitative approach. This study used a qualitative description. Five English teachers were involved. The researcher collected the data as interview, and observation. Referring to the finding of the study, based on result of interview found the teachers problems used target language in teaching learning process, such as; the low vocabulary of the students, the ability of English skill of the students, the situation in the classroom did not support the use of target language, the time was not effective. Based on the findings of classroom observation in classroom the teacher delivered used the target language in simple sentence on greeting, giving instruction, asking question, delivering materials and closing.